Władza przypadkowa czy wypadkowa? Komunikacyjna siła użytkowników mediów społecznościowych - Kampka, Agnieszka (Kultura i Społeczeństwo, 2024)
Taking the fandom of the Korean band BTS as an example, the article describes new opportunities for communicative influence by ordinary social media users. Based on a literature review and an analysis of the fandom’s activities, the author discusses the specific challenges of media competence in social media, and reflects on the potential forms and purposes of the new digital mass.